SOCIAL STUDIES LEARNING USING MICROSOFT TEAMS APPLICATION: AN ATTEMPT TO IMPROVING STUDENT LEARNING OUTCOMES - Ervina Halit; Muhammad Turhan Yani; Sarmini, Sarmini (Bajang Institute, 2024)
This study was conducted to improve student learning outcomes in social studies subjects on economic activities taught using the Microsoft Teams application. This Classroom Action Research (PTK) was conducted on students of class VII A SMPI PB Soedirman Bekasi on the material of economic activities. The subjects in this study were 30 students of class VII A. The implementation of the application of Microsoft Teams for Classroom Action Research activities was carried out in two cycles, where each cycle consisted of 2 meetings and 1 test. Each cycle was two meetings and one test, with one meeting lasting 2 x 40 minutes. The results of the research in the first cycle using the Microsoft Teams application obtained student scores of 47%. In the second cycle when using the Microsoft Team application obtained student results of 78%. That way, student learning outcomes can increase after using the Microsoft Teams application